1977
DOI: 10.1007/bf02402146
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte changes and acid base balance after alcohol withdrawal

Abstract: 70 chronic alcoholics in the withdrawal state, 45 with convulsions and 25 controls without convulsive seizures, were tested with respect to electrolyte changes and acid base balance in serum or blood and cerebrospinal fluid (CSF). It was of special interest to note that there was a partial independence between magnesium levels in serum and CSF. Thus the serum level has only a limited liability as to magnesium depletion suggested to be responsible for seizure precipitation. In the seizure group a slightly but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Laso et al (1990) also showed a close negative correlation between intensity of withdrawal and serum potassium. Meyer and Urban (1977) revealed a significant decrease of potassium in their group of alcoholics with withdrawal seizures. Serum potassium remained within the normal range (although low) in their control group (withdrawing alcoholics without seizures).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laso et al (1990) also showed a close negative correlation between intensity of withdrawal and serum potassium. Meyer and Urban (1977) revealed a significant decrease of potassium in their group of alcoholics with withdrawal seizures. Serum potassium remained within the normal range (although low) in their control group (withdrawing alcoholics without seizures).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of published reports showing that serum potassium concentration falls during alcohol withdrawal, especially if complicated by delirium tremens (Meyer and Urban, 1977;Wadstein and Skude, 1978;Watson et al, 1984;Laso et al, 1990;Carl and Holzbach, 1994;Wetterling et al, 1994). Some studies even show evidence that potassium could be useful as an indicator to predict delirium tremens (Wadstein and Skude, 1978;Wetterling et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the same study phosphate was investigated in 22 patients at admission, three had a low, and three a high plasma phosphate concentration. Other investigators studied electrolytes in patients with mild or moderate alcohol withdrawal symptoms (but not DT), and in both studies cerebrospinal fluid (CSF) and plasma calcium were within normal range (8,9).…”
mentioning
confidence: 99%